2020
DOI: 10.1088/1402-4896/abb4f7
|View full text |Cite
|
Sign up to set email alerts
|

Optoelectronic investigations of needle-shaped Zn1-xSnxO nanoparticles synthesized by coprecipitation method

Abstract: In this work, Zn1-xSnxO (x = 0, 0.01, 0.02, 0.04, 0.06 and 0.1) nanoparticles were synthesized via the coprecipitation method. The prepared nanoparticles were characterized by x-ray powder diffraction (XRD), transmission electron microscope (TEM) and Fourier transform infrared spectroscopy (FTIR). The optical investigations were utilized by UV–vis spectroscopy (UV) and photoluminescence (PL). Moreover, the electrical studies were performed through dc conductivity and dielectric measurements. The successful Sn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…In addition, some studies have shown that rod-shaped nanoparticles have a higher dispersibility in a medium due to a higher surface–volume ratio . More surface atoms are present in the rod-shaped morphology, increasing the chemical reactivity of the prepared nanoparticles . At the same time, the luminescence centers associated with the presence of dopant ions close to the surface of the nanoparticle will also have different properties than those in the volume of the nanoparticle, being more sensitive to changes in its environment, making rod-like morphology suitable for specific applications such as optical markers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some studies have shown that rod-shaped nanoparticles have a higher dispersibility in a medium due to a higher surface–volume ratio . More surface atoms are present in the rod-shaped morphology, increasing the chemical reactivity of the prepared nanoparticles . At the same time, the luminescence centers associated with the presence of dopant ions close to the surface of the nanoparticle will also have different properties than those in the volume of the nanoparticle, being more sensitive to changes in its environment, making rod-like morphology suitable for specific applications such as optical markers.…”
Section: Resultsmentioning
confidence: 99%
“…15 More surface atoms are present in the rod-shaped morphology, increasing the chemical reactivity of the prepared nanoparticles. 54 At the same time, the luminescence centers associated with the presence of dopant ions close to the surface of the nanoparticle will also have different properties than those in the volume of the nanoparticle, being more sensitive to changes in its environment, making rod-like morphology suitable for specific applications such as optical markers. Well-crystallized Eu 3+ :YPO 4 nanorods were obtained by conventional hydrothermal process only after prolonged thermal treatments at 200 °C (for 12−18 h), 19,23 4 In our case, this morphology was obtained at much lower treatment times with considerable time and energy savings.…”
Section: Tem Analysismentioning
confidence: 99%
“…Figure 14 represents the Tauc plots of all the prepared nanoparticles [67]. From the obtained values, listed in table 2, it can be noticed that the direct band gap energy (E g ) d increases as the codopant concentration increases.…”
Section: Uv-vis Spectroscopymentioning
confidence: 95%
“…The x-ray density ( ), the dislocation density (δ), and the specific surface area (S) were calculated using the following equations (El-Fadl et al, 2019;Kamareddine et al, 2020):…”
Section: Nanoparticles Characterizationmentioning
confidence: 99%